2015
DOI: 10.3389/fmicb.2015.01315
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Pre-neck Appendage Protein (Dpo7) from Phage vB_SepiS-phiIPLA7 as an Anti-biofilm Agent in Staphylococcal Species

Abstract: Staphylococcus epidermidis and Staphylococcus aureus are important causative agents of hospital-acquired infections and bacteremia, likely due to their ability to form biofilms. The production of a dense exopolysaccharide (EPS) matrix enclosing the cells slows the penetration of antibiotic down, resulting in therapy failure. The EPS depolymerase (Dpo7) derived from bacteriophage vB_SepiS-phiIPLA7, was overexpressed in Escherichia coli and characterized. A dose dependent but time independent response was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 66 publications
2
84
0
Order By: Relevance
“…Pectate/pectin lyases are characterized by cleavage of the α-1,4 bonds of polygalacturonic acid. Enzymes possessing such domain have been described for Pseudomonas phages Φ15 and AF (Cornelissen et al 2011, 2012), Klebsiella phages (NTUH-K2044-K1–1, KP36) (Lin et al 2014; Majkowska-Skrobek et al 2016), Vibrio phage JA1 (Linnerborg et al 2001), and Staphylococcus phage vB_SepiS-ΦIPLA7 (Gutierrez et al 2015) (Table 1). Alginate lyases (mannuronate or guluronate lyases) characteristic for Pseudomonas and Azobacter phages (PT6) are able to degrade the α-1,4 bond of alginate, a linear polysaccharide of β-D-mannuronate, and its C5 epimer α-L-guluronate common for mucoid strains infecting cystic fibrosis patients (Davidson et al 1977; Wong et al 2000; Glonti et al 2010) (Table 1).…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pectate/pectin lyases are characterized by cleavage of the α-1,4 bonds of polygalacturonic acid. Enzymes possessing such domain have been described for Pseudomonas phages Φ15 and AF (Cornelissen et al 2011, 2012), Klebsiella phages (NTUH-K2044-K1–1, KP36) (Lin et al 2014; Majkowska-Skrobek et al 2016), Vibrio phage JA1 (Linnerborg et al 2001), and Staphylococcus phage vB_SepiS-ΦIPLA7 (Gutierrez et al 2015) (Table 1). Alginate lyases (mannuronate or guluronate lyases) characteristic for Pseudomonas and Azobacter phages (PT6) are able to degrade the α-1,4 bond of alginate, a linear polysaccharide of β-D-mannuronate, and its C5 epimer α-L-guluronate common for mucoid strains infecting cystic fibrosis patients (Davidson et al 1977; Wong et al 2000; Glonti et al 2010) (Table 1).…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%
“…Depolymerases described and characterized to date are present in the phage virion within tail fibers or tailspikes on the baseplate, regardless of the phage family they originate from or the host bacterial species they infect (Table 1). One described exception is the depolymerase encoded by Staphylococcus phage vB_SepiS-ΦIPLA7, which shows 99% homology with a pre-neck appendage protein (Gutierrez et al 2015). Generally, depolymerases form elongated homotrimers that appear as protruding cell-puncturing devices on the virion, which aligns well with their biological function.…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%
“…Moreover, numerous studies have already shown the ability of phages to remove biofilms formed by a variety of bacteria, including staphylococcal species (15)(16)(17)(18). Additionally, phage-encoded proteins, such as endolysins and exopolysaccharide depolymerases, can also be used for biofilm removal (19)(20)(21). Nevertheless, most studies available to date have focused on single-species communities, while only limited work has tackled the elimination of polymicrobial biofilms with phage-based products (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Gutiérrez et al. () applied an exopolysaccharide depolymerase, Dpo7, to remove the biofilm formed by S. epidermidis and S. aureus in 24 hr. They found that the biofilms were removed by up to 27% to 85% in all exopolysaccharide‐producing bacteria, with the highest activity in S. epidermidis strain Z2LDC14.…”
Section: Proteolytic Enzymesmentioning
confidence: 99%
“…Moreover, a number of phage-encoded proteins have been found to have polysaccharide depolymerase-like activities that act specifically on polysaccharide or polysaccharide-derived molecules. Gutiérrez et al (2015) applied an exopolysaccharide depolymerase, Dpo7, to remove the biofilm formed by S. epidermidis and S. aureus in 24 hr. They found that the biofilms were removed by up to 27% to 85% in all exopolysaccharide-producing bacteria, with the highest activity in S. epidermidis strain Z2LDC14.…”
Section: Bacteriophage Lysinsmentioning
confidence: 99%